2006
DOI: 10.1073/pnas.0511150103
|View full text |Cite
|
Sign up to set email alerts
|

Identification of distinct molecular phenotypes in acute megakaryoblastic leukemia by gene expression profiling

Abstract: Individuals with Down syndrome (DS) are predisposed to develop acute megakaryoblastic leukemia (AMKL), characterized by expression of truncated GATA1 transcription factor protein (GATA1s) due to somatic mutation. The treatment outcome for DS-AMKL is more favorable than for AMKL in non-DS patients. To gain insight into gene expression differences in AMKL, we compared 24 DS and 39 non-DS AMKL samples. We found that non-DS-AMKL samples cluster in two groups, characterized by differences in expression of HOX͞TALE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
198
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(213 citation statements)
references
References 30 publications
14
198
0
1
Order By: Relevance
“…This is analogous to another chromosome 21-localized gene, AML1, which was downregulated in DS AMkL compared to non-DS AMkL. 24 Using an inducible expression system in K562 cells, we found that overexpression of ETS2 was associated with increased expression of the megakaryocytic cell surface markers, CD41 and CD61, independent of GATA1 levels. This suggests that ETS2 may play important roles in the AMkL phenotype in both DS and non-DS children.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…This is analogous to another chromosome 21-localized gene, AML1, which was downregulated in DS AMkL compared to non-DS AMkL. 24 Using an inducible expression system in K562 cells, we found that overexpression of ETS2 was associated with increased expression of the megakaryocytic cell surface markers, CD41 and CD61, independent of GATA1 levels. This suggests that ETS2 may play important roles in the AMkL phenotype in both DS and non-DS children.…”
Section: Discussionmentioning
confidence: 52%
“…23 Most recently, it was reported that transcripts for AML1b and AML1c, the two larger isoforms of AML1, are downregulated in DS megakaryoblasts compared to non-DS megakaryoblasts, suggesting that AML1 is linked to the megakaryocytic lineage. 24 In addition to its gene dosage effects, AML1 coexpresses and cooperates with GATA1 in megakaryocytic differentiation. 25 ETS2 and ERG (ETS transcription factor family members) have been shown to be overexpressed in adult myeloid leukemia cases with complex acquired karyotypes involving chromosome 21.…”
Section: Introductionmentioning
confidence: 99%
“…GATA-1 amino-terminal sequences are required for maximal transactivation (9), but the underlying mechanisms are unknown. Gene expression profiling in megakaryoblasts from GATA-1s transgenic mice demonstrated that GATA-1 target genes are differentially deregulated (39,46). We reasoned that mutations impairing GATA-1 activity preferentially affect target genes requiring high GATA-1 activity.…”
Section: Deletion Of the Gata-1 Amino Terminus Severely Deregulates Amentioning
confidence: 99%
“…1 Interestingly, the 11q14-21 region had previously been identified as a cluster of uncommon breakpoints in AMKL (1), but the CALM-AF10 translocation could not be detected by conventional cytogenetics in two larger series that included up to 72 patients with AMKL. 2,3 However, the fact that we had identified a subgroup of non-DS AMKL cases with marked increase of HOXA cluster gene expression, which was reminiscent of the HOXA cluster gene expression profiles reported in CALM-AF10 positive T-cell acute lymphoblastic leukemias (T-ALLs), 4,5 prompted us to search for cryptic CALM-AF10 translocations in non-DS AMKL.…”
mentioning
confidence: 89%